Punishment Motives for Small and Big Lies. Issue 2 (2nd February 2017) - Eisenkopf, Gerald; Gurtoviy, Ruslan; Utikal, Verena
Abstract : Corporate fraud typically involves deceptive financial statements that are harmful for some stakeholders. We analyze how preferences for honesty and economic fairness shape the punishment of such untruthful statements. Our laboratory experiment disentangles the crucial confound that, for deceptive financial statements, larger deviations from the truth imply both a stronger violation of the honesty norm and an increase in economic harm. Our study measures how people punish increased dishonesty controlling for the corresponding economic harm. We find that punishment increases with the size of the lie. This behavioral pattern is driven by people who are honest themselves. Our results suggest that popular demand for punitive measures in case of financial scandals reflects a genuine interest in the enforcement of social norms.